International Delphi Expert Consensus on Safe Return to Surgical and Endoscopic Practice: From the Coronavirus Global Surgical Collaborative. Issue 1 (July 2021) - Asbun, Horacio J.; Abu Hilal, Mohammad; Kunzler, Filipe; Asbun, Domenech; Bonjer, Jaap; Conlon, Kevin; Demartines, Nicolas; Feldman, Liane S.; Morales-Conde, Salvador; Pietrabissa, Andrea; Pryor, Aurora D.; Schlachta, Christopher M.; et al.
Abstract : Objective: The aim of this work is to formulate recommendations based on global expert consensus to guide the surgical community on the safe resumption of surgical and endoscopic activities. Background: The COVID-19 pandemic has caused marked disruptions in the delivery of surgical care worldwide. A thoughtful, structured approach to resuming surgical services is necessary as the impact of COVID-19 becomes better controlled. The Coronavirus Global Surgical Collaborative sought to formulate, through rigorous scientific methodology, consensus-based recommendations in collaboration with a multidisciplinary group of international experts and policymakers. Methods: Recommendations were developed following a Delphi process. Domain topics were formulated and subsequently subdivided into questions pertinent to different aspects of surgical care in the COVID-19 crisis. Forty-four experts from 15 countries across 4 continents drafted statements based on the specific questions. Anonymous Delphi voting on the statements was performed in 2 rounds, as well as in a telepresence meeting. Results: One hundred statements were formulated across 10 domains. The statements addressed terminology, impact on procedural services, patient/staff safety, managing a backlog of surgeries, methods to restart and sustain surgical services, education, and research. Eighty-three of the statements were approved during the first round of Delphi voting, and 11 during the second round. A final telepresence meeting and discussion yielded acceptance of 5 other statements. Conclusions: The Delphi process resulted in 99 recommendations. These consensus statements provide expert guidance, based on scientific methodology, for the safe resumption of surgical activities during the COVID-19 pandemic. Abstract : Supplemental Digital Content is available in the text